The Role of Principal Management in Improving Teacher Performance - Hasriani, Hasriani; Rosma, Rosma; L, Kasmawati (CV. Rayyan Dwi Bharata, 2023)
This study aims to analyze the role of the principal in improving teacher performance in the school environment. Writing this article uses the Literature Review approach, namely book reviews, journals, papers, notes and sources related or relevant to the research topic to form the basis of this research. In this literature analysis, several important findings can be identified. First, the principal has an important role to play in creating a work environment that supports and motivates teachers to improve their performance. Principals need to provide clear direction, provide adequate support and resources, and involve teachers in making decisions related to learning and curriculum development. Second, the principal plays a role in developing and facilitating training and professional development for teachers. Providing relevant and ongoing training, principals can help teachers improve their skills, update their knowledge, and implement best practices in teaching. Third, the principal also plays a role in providing constructive feedback and evaluating teacher performance. Through regular and continuous classroom observations and performance appraisals, principals can identify teachers' strengths and weaknesses and provide feedback that focuses on their professional development. In the context of this research, the role of principal management in improving teacher performance is very important. By creating a supportive environment, providing relevant training and constructive feedback, principals can contribute significantly to improving the quality of teaching in schools.